TINGKAT KERAWANAN KEBAKARAN HUTAN DAN LAHAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (SIG) DI KOTA AMBON (STUDI KASUS DI JAZIRAH LEITIMUR SELATAN) - Aldi Herdian; Aryanto Boreel; Ronny Loppies (JURNAL HUTAN PULAU-PULAU KECIL, 2021)
Limited data and the lack of use of Remote Sensing Technology and Geographic Information Systems (GIS) to map areas that are potentially prone to forest and land fires in Ambon City are one of the obstacles in handling forest and land fires. This study aims to identify the factors that cause forest and land fires, determine the level of vulnerability to forest and land fires and produce a digital map of forest and land fires in Jazirah Leitimur Selatan, Ambon City. The data used are Landsat 8 OLI/TIRS C1 Level-1 path/row 109/62 satellite imagery acquired on October 28, 2017. Hotspot data was obtained from FIRMS and Lapan Fire Hotspot. Data processing is done by using the method of overlaying variables that trigger the occurrence of forest and land fires. The results showed that the Jazirah Leitimur Selatan has the potential to be prone to forest and land fires with 76.6% of the area included in the vulnerable to very vulnerable category, while 23.4% is in the non-prone category.